Impacts of postweaning growth rate of replacement beef heifers on their reproductive development and productivity as primiparous cows. (14th August 2019) - Schubach, Kelsey M; Cooke, Reinaldo F; Brandão, Alice P; Schumaher, Thiago F; Pohler, Ky G; Bohnert, David W; Marques, Rodrigo S
Abstract: This experiment evaluated the effects of postweaning body weight (BW) gain of replacement beef heifers on their reproductive development and productivity as primiparous cows. Seventy-two Angus × Hereford heifers were ranked on day −6 of experiment (17 d after weaning) by age and BW (218 ± 1.6 d of age and 234 ± 3 kg of BW), and assigned to receive 1 of 3 supplementation programs from days 0 to 182: 1) no supplementation to maintain limited BW gain (LGAIN ), 2) supplementation to promote moderate BW gain (MGAIN ), or 3) supplementation to promote elevated BW gain (HGAIN ). Heifers were maintained in 2 pastures (36 heifers/pasture, 12 heifers/treatment in each pasture) with free-choice alfalfa-grass hay, and supplements were offered individually 6 d per week. Heifer shrunk BW was recorded on days −6 and 183 for average daily gain (ADG) calculation. Blood samples were collected for puberty evaluation via plasma progesterone weekly from days 0 to 182. On day 183, heifers were combined into a single group and received the same nutritional management until the end of the experimental period (day 718). From days 183 to 253, heifers were assigned to a fixed-time artificial insemination program combined with natural service. Average daily gain from days 0 to 182 was greater ( P < 0.01) in HGAIN vs. MGAIN and LGAIN (0.78, 0.60, and 0.37 kg/d, respectively; SEM = 0.02), and greater ( P < 0.01) in MGAIN vs. LGAIN heifers. Puberty attainment by the beginning of the breeding season was also greater in HGAIN vs. MGAIN and LGAIN (87.5%, 62.5%, and 56.5%, respectively; SEM = 7.1) but similar ( P = 0.68) between MGAIN vs. LGAIN heifers. A treatment × day interaction was detected ( P < 0.01) for calving rate, as HGAIN heifers calved earlier compared with MGAIN and LGAIN heifers. Ten heifers per treatment were assessed for milk production via weigh-suckle-weigh at 56.8 ± 1.5 d postpartum, followed by milk sample collection 24 h later. No treatment differences were detected ( P ≥ 0.16) for milk yield and composition. However, mRNA expression of GLUT1 in milk fat globules was less ( P ≤ 0.02) in LGAIN vs. MGAIN and HGAIN heifers, and expression of GLUT8 mRNA was also less ( P = 0.04) in LGAIN vs. HGAIN heifers. No treatment differences were detected ( P ≥ 0.44) for offspring weaning BW. Collectively, results from this experiment indicate that HGAIN hastened the reproductive development of replacement heifers, without negatively affecting their milk productivity and offspring weaning weight as primiparous cows.